KONSEP JIWA DALAM PSIKOLOGI IBNU MISKAWAIH SEBAGAI DASAR PENDIDIKAN MORAL REMAJA - Safinatun Naja (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The contemporary moral crisis among adolescents has become a central issue demanding a multidisciplinary approach, particularly through a synthesis of classical Islamic philosophy and modern psychology. One relevant thinker in this context is Ibn Miskawayh, an 11th-century Muslim philosopher and ethicist who offers a profound vision of character formation through gradual and balanced soul development. This study aims to explore the relevance of Ibn Miskawayh’s philosophical psychology in shaping the ethics and psychological balance of today’s youth. This research employs a qualitative-descriptive approach with literature analysis of Ibn Miskawayh’s major work, Tahdhīb al-Akhlāq, as well as contemporary studies in developmental psychology and moral education. The study focuses on three core principles in his moral pedagogy: tawazun (balance), tadrij (gradual development), and sa'adah (happiness), along with the soul’s tripartite structure vegetative, animalistic, and rational. Findings suggest that Ibn Miskawayh’s moral education model strongly aligns with modern psychological theories and has the potential to serve as an alternative framework for integrative character education. The pedagogical implications include applying a spiritual-rational approach in school curricula and enhancing the role of teachers and counselors as philosophical and reflective moral guides.